THE SYSTEM ANALYSIS OF TRAFFIC PROVIDER TO IDENTIFY A DISTRIBUTED DENIAL OF SERVICE CHANNEL - Raman Aydin Mamedov (Современная наука и инновации)
This article considers the standard method of detecting distributed denial of service through monitoring and analysis of three-layer network model OSI. A new method of evaluation of the threat developed, it based on monitoring the physical layer network model and the analysis of its content and using fuzzy logic.